Characterizing ecomorphological patterns in hyenids: a multivariate approach using postcanine dentition - Carlos Coca-Ortega; Juan Antonio Pérez-Claros (PeerJ, 2019)
We analyze the multivariate pattern of lower and upper cheek dentition for the family Hyaenidae along its evolutionary history. A total of 11,698 individual measurements of lengths and widths for the main postcanine teeth were collected for 54 extinct and three extant species of this family and analyzed by means of principal component analyses. Our results indicate that the functional aspects are better reflected by lower cheek dentition as a result of mosaic evolution. The multivariate structure captured by the three first principal components correspond to different adaptive strategies. The two first components characterize the main groups of ecomorphs, while hunting species separate from scavengers along the third axis. In the context of Hyaenidae, the post-canine cheek dentition of Parahyaena brunnea and Hyaena hyaena shows an extreme degree of specialization in scavenging.